Plant protein-coding gene families: Their origin and evolution - Fang, Yuanpeng; Jiang, Junmei; Hou, Xiaolong; Guo, Jiyuan; Li, Xiangyang; Zhao, Degang; Xie, Xin (Frontiers in Plant Science, 2022)
Steady advances in genome sequencing methods have provided valuable insights into the evolutionary processes of several gene families in plants. At the core of plant biodiversity is an extensive genetic diversity with functional divergence and expansion of genes across gene families representing unique phenomena. The evolution of gene families underpins the evolutionary history and development of plants and is the subject of this review. We discuss the implications of the molecular evolution of gene families to plants, as well as the potential contributions, challenges, and strategies associated with investigating phenotypic alterations to explain the origin of plants and their tolerance to environmental stresses.